It Obliges You to Do Things You Normally Wouldn’t: Organizing and Consuming Private Life in the Age of Airbnb - Bruni, Attila; Esposito, Fabio Maria (PARTECIPAZIONE E CONFLITTO, 2019)
In what ways do everyday life and private spaces become productive elements for platform organizations? Referring to a research on Airbnb (a platform-based company and current leader at the global level in the online hospitality industry) recently conducted in a touristic north-eastern Italian province, this paper critically explores to what degree and how Airbnb pervades, changes and controls the Hosts’ domestic space and spare time. To do so, first we will concentrate on the elements that regulate the relationship between the user and the platform and on some of the processes and mechanisms implied by the platform architecture. Then, by describing the everyday practices of "house-management" enacted by the Hosts, we will highlight the invisible work involved in ’performing the platform’. From this point of view, it is worth noticing how, although Airbnb does not aim to create a parallel labour market, it produces ’platform workers’ anyway, in that it implies the active engagement of its users in concrete activities. Airbnb is thus a perfect case to look at the ways in which platform organizations engage users in forms of production previously unknown, turning private goods and time into productive elements.